2013
DOI: 10.3390/md11030623
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of Conotoxins

Abstract: Conotoxins are small peptides present in the venom of cone snails. The snail uses this venom to paralyze and capture prey. The constituent conopeptides display a high level of chemical diversity and are of particular interest for scientists as tools employed in neurological studies and for drug development, because they target with exquisite specificity membrane receptors, transporters, and various ion channels in the nervous system. However, these peptides are known to contain a high frequency and variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…The best characterized of these AMPs is styelin D, which possesses α-helical structure and is highly unusual in that it contains twelve post-translationally modified residues [77]. For example, the peptide contained multiple bromotryptophan residues, which are found in the AMPs of other marine organisms [218,219,220,221,222] and play an important role in the life of sea sponges and lower marine invertebrates [223]. Styelin D’s post-translationally modified residues enhanced the peptide’s membranolytic action at low pH but only against Gram-positive bacteria.…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%
“…The best characterized of these AMPs is styelin D, which possesses α-helical structure and is highly unusual in that it contains twelve post-translationally modified residues [77]. For example, the peptide contained multiple bromotryptophan residues, which are found in the AMPs of other marine organisms [218,219,220,221,222] and play an important role in the life of sea sponges and lower marine invertebrates [223]. Styelin D’s post-translationally modified residues enhanced the peptide’s membranolytic action at low pH but only against Gram-positive bacteria.…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%
“…[20] Nevertheless,s nake toxins are predominantly reported to possess N-linked glycosylation, especially serine proteases,w here the glycan may modulate the protease catalytic activity. [22] Then onglycosylated (TcNPa-ng) and glycosylated (TcNPa) peptides were synthesized using standard Fmoc solid-phase peptide synthesis on Fmoc-serine-Wang resin (see Figure S3 in the Supporting Information). The glycan, Gal-GalNAc,i sl inked to inhibiting proteolytic degradation and gave two orders of magnitude greater potencya sa na nalgesic than the nonglycosylated form.…”
Section: Methodsmentioning
confidence: 99%
“…The glycan, Gal-GalNAc,i sl inked to inhibiting proteolytic degradation and gave two orders of magnitude greater potencya sa na nalgesic than the nonglycosylated form. [22] Then onglycosylated (TcNPa-ng) and glycosylated (TcNPa) peptides were synthesized using standard Fmoc solid-phase peptide synthesis on Fmoc-serine-Wang resin (see Figure S3 in the Supporting Information). Evaluation of their secondary structures was undertaken by circular dichroism (CD) analysis in 50 %T FE/H 2 Oa nd 50 %H FIP/H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it is worth noting that some animals use glycosylated, neurotoxic peptides as a self-defense mechanism. Many cone snails use a glycosylated conotoxins to paralyze attackers (Gerwig et al, 2013 ). Olivera and coworkers (Craig et al, 1999 ), among others, synthesized non-glycosylated versions of a number of these peptides, and found that although the non-glycosylated versions showed improved neurotensin receptor binding affinity compared with the native, glycosylated peptides, the native peptides still showed a greater than 10-fold increase in i.v .…”
Section: Benefits and Disadvantages Of Carbohydrate Incorporationmentioning
confidence: 99%